Employer Engagement in Curriculum Making Process in Nepal: Meaningful or Cosmetic? - Bajracharya, Anil Muni; Paudel, Prakash Kumar (Journal of Technical and Vocational Education and Training, 2021)
The engagement of employers in the education system is interpreted on the assumption that it enables a student to enhance the knowledge according to the market demand. This helps to furnish students with skills and knowledge directly relevant to generating employment, familiarize the workplace environment, and reduce the constraints in transitioning from learning to work. The partaking of employers in curriculum preparation not only supports to increase the involvement of employers but also helps to prepare the market-based curriculum. More so, stakeholder participation in TVET curriculum preparation is crucial. However, employer engagement in the curriculum making process, in general, has been a neglected agenda. Against this backdrop, we examined the level of employer engagement in TVET curriculum making process in Nepal. We interviewed 79 individual national employers asking their level of participation in curriculum making process. Among the participants, four were further interacted to understand the reason for minimum participation. The employers, on the one hand, shared that their participation is just for participation to fulfil the requirement provisioned by law. On the other hand, they also said their inputs rarely incorporated in the process even if they had involved in the curriculum design phase. In this sense, the participation of the employer in the curriculum-making process has become cosmetic in practice rather than desired and meaningful.